Effects of Aerobic Exercise on Depression and CD4 Counts in People Living with HIV - Untung Sujianto; Madya Sulisno; Richal Grace Zefanya Uly (Jurnal Ners, 2021)
Introduction: HIV patients often experience psychological and physical disorders which greatly affect the adherence of people living with HIV/AIDS (PLWHA). This study aimed to assess the effects of aerobic exercise on the levels of depression and CD4 cell count of HIV patients.Methods: This study used a pre-post quasi-experimental design with a control group. The sampling technique was consecutive sampling, with a total sample of 52 HIV respondents. Depression level was measured using the Beck Depression Inventory (BDI), while CD4 count was measured using the Pyma analyser. The aerobic exercise intervention was given three times a week with a duration of 20-30 minutes each for four weeks. The collected data were analysed using a paired sample t-test and an independent sample t-test.Results: The results showed a significant difference in the mean value of depression before and after the intervention of aerobic exercise (M =25.15 and M=22.46, respectively) with p = 0.001. Similarly, there was a significant difference in the mean of CD4 counts between the control group (M=303.38) and the intervention group (M=305.38) after the intervention with p = 0.031.Conclusion: Aerobic exercise is effective in reducing depression levels and increasing CD4 counts in HIV patients. Immune system cells circulate more rapidly and there is a boost in the production of macrophages, cells that can attack bacteria.